Synthesis of Nickel Oxide Nanoparticles from Syzygium cumini Plant Fruit Pulp Extract: Study of their Antibacterial, Antifungal and Cytotoxic Activities on CHO Cells - Ammadu Kolahalam, Lalitha; Prasad, K.R.S.; Murali Krishna, P.; Supraja, N. (Asian Journal of Chemistry, 2022)
The nickel oxide nanoparticles were synthesized using Syzygium cumini plant fruit pulp in a simple, ecofriendly and cost-effective procedure using the green chemistry route. The prepared nickel oxide nanoparticles were characterized by UV-visible (UV-Vis), Fourier transform infrared (FT-IR) spectroscopy, powder X-ray diffraction spectrometry (XRD), zeta potential (ZE), particle size (DLS), field emission scanning electron microscope (FE-SEM) analysis. The synthesized nanoparticles showed on an average of 16 to 31 nm in size. The synthesized nanoparticles were tested on several Gram-positive and Gram-negative bacteria and also on fungi, which showed less toxicity to them. Finally, the synthesized nanoparticles cytotoxic activity was tested on Chinese Hamster Ovary (CHO) cell lines, which showed cytotoxicity with IC50 value of 2.66 μg/mL.